Prognostic relevance of demographics and surgical practice for patients with gastric cancer in two centers: in Poland versus Germany - Jaworski, Radoslaw (Springer Japan, 2011)
BACKGROUND: Although studies comparing the surgical treatment of gastric carcinoma in Japan and Western industrialized countries have revealed differing survival rates, no studies to date have been performed comparing Western and Eastern Europe. This study aimed to compare demographics and surgical practice as well as the related prognostic impact on gastric cancer patients treated in Poland and Germany. METHODS: This retrospective study included gastric cancer patients treated between 1999 and 2004 by surgical departments in Gdansk (Poland) and Cologne (Germany). Univariate and multivariate analyses of demographic, histopathological, surgical, and prognostic data were performed. RESULTS: Included were 117 patients from Gdansk and 130 patients from Cologne. The Cologne patients showed higher incidence rates of serious comorbidity, pT1 cancer, and distant metastasis than those from Gdansk. Indications for and frequency of selected surgical procedures differed significantly. D2-lymphadenectomy was performed in 89% of the Cologne patients, while D1-lymphadenectomy was done for 85% of the Gdansk patients. Univariate analysis yielded a 5-year survival rate of 28.3% for the Gdansk patients, and 40.3% for the Cologne patients (p = 0.056). Independent prognostic factors were pT category (p = 0.002), pN category (p < 0.001), pM category (p = 0.027), residual tumor (R) category (p = 0.004), age (p = 0.012), and number of resected lymph nodes (p = 0.005). CONCLUSIONS: Significant differences of clinical and surgical parameters exist between gastric cancer patients treated in Poland and Germany. In addition to established independent prognostic factors, we found that survival improved with each additionally resected lymph node.